2023
DOI: 10.1371/journal.pgen.1010705
|View full text |Cite
|
Sign up to set email alerts
|

Fob1-dependent condensin recruitment and loop extrusion on yeast chromosome III

Abstract: Despite recent advances in single-molecule and structural analysis of condensin activity in vitro, mechanisms of functional condensin loading and loop extrusion that lead to specific chromosomal organization remain unclear. In Saccharomyces cerevisiae, the most prominent condensin loading site is the rDNA locus on chromosome XII, but its repetitiveness deters rigorous analysis of individual genes. An equally prominent non-rDNA condensin site is located on chromosome III (chrIII). It lies in the promoter of a p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 78 publications
1
6
0
Order By: Relevance
“…In terms of mechanism, published ChIP-seq data shows strong binding of condensin on the right side of RE near the ARS304 and RDT1 gene 40 , and deletion of this region abolishes the mating typedependent Hi-C pattern of ChrIII 36 . Consistent with this observation, we found that the depletion of condensin subunit Smc2 compromises the MTAC signal between MATa and RE.Functionally, condensin depletion impairs mating-type switch efficiency and donor preference40,42 . Together, this data provides strong support for the model that condensin mediates the looping between MATa and RE to promote the usage of HML as the sequence donor.Finally, by comparing the proximity of NDRs to different VPs, a few major spatial patterns start to emerge.…”
supporting
confidence: 85%
See 3 more Smart Citations
“…In terms of mechanism, published ChIP-seq data shows strong binding of condensin on the right side of RE near the ARS304 and RDT1 gene 40 , and deletion of this region abolishes the mating typedependent Hi-C pattern of ChrIII 36 . Consistent with this observation, we found that the depletion of condensin subunit Smc2 compromises the MTAC signal between MATa and RE.Functionally, condensin depletion impairs mating-type switch efficiency and donor preference40,42 . Together, this data provides strong support for the model that condensin mediates the looping between MATa and RE to promote the usage of HML as the sequence donor.Finally, by comparing the proximity of NDRs to different VPs, a few major spatial patterns start to emerge.…”
supporting
confidence: 85%
“…Previous studies indicate that RE, Sir2, and condensin are important for MATa interactions 40,42 . To test if these elements indeed lead to changes of MTAC signals, we constructed strains containing a RE or SIR2 gene deletion, or auxin-degradable Smc2 (Smc2-AID) ( Materials and Methods ).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…In fission yeast and Candida albicans , monopolin proteins (Lrs4-Csm1/Mde4-Pcs1) promote the centromeric enrichment of condensin and to prevent merotely 3436 . Similarly, monopolin (Lrs4-Csm1) is important for condensin localization and function within the rDNA and mating locus in budding yeast 37,38 . In Xenopus egg extracts, the general transcription factor TFIIH promotes the enrichment of condensin on chromatin, though this may be indirect 39 .…”
Section: Introductionmentioning
confidence: 99%